(untitled) (Revista Brasileira Multidisciplinar, 2025)
Childbirth gradually became a hospital intervention that changed the levels of care. Surgical delivery made difficult deliveries safer and, consequently, reduced the risk of mother and baby death, resulting in increasingly high numbers of cesarean sections, which are sometimes unnecessary. This study aimed to characterize the prevalence of delivery routes performed in Brazil, comparing rates between different regions of the country, and identifying the maternal mortality rate associated with childbirth complications, between the years 2011 and 2021. This is an ecological study performed by obtaining data available on the TabNet DATASUS platform. The data obtained were tabulated in Excel, and, then, they were statistically analyzed in the program BioEstat 5.3. It was observed that the regions with emphasis on the cesarean section rate throughout the historical series were: Northeast, North, Midwest and South. On the other hand, the Southeast showed a significant, strong and positive correlation between mortality rates and the prevalence of vaginal delivery (p<0,01 e r=0,80) and significant, strong and negative correlation between mortality rates and the prevalence of cesarean sections (p<0,01 e r=-0,80). At the end, cesarean rates in Brazil increased gradually over the years studied, and accompanied an increase in the associated maternal mortality rate.